2019
DOI: 10.1080/15548627.2019.1596478
|View full text |Cite
|
Sign up to set email alerts
|

RAB2 regulates the formation of autophagosome and autolysosome in mammalian cells

Abstract: Multiple sources contribute membrane and protein machineries to construct functional macroautophagic/autophagic structures. However, the underlying molecular mechanisms remain elusive. Here, we show that RAB2 connects the Golgi network to autophagy pathway by delivering membrane and by sequentially engaging distinct autophagy machineries. In unstressed cells, RAB2 resides primarily in the Golgi apparatus, as evidenced by its interaction and colocalization with GOLGA2/GM130. Importantly, autophagy stimuli disso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
76
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(83 citation statements)
references
References 89 publications
5
76
1
Order By: Relevance
“…However, we detected a 3fold increase in the incidence of somatic structures resembling autophagocytic organelles in rab2 mutants ( Fig. S5D), potentially interesting in connection with the previously reported function of RAB2 in autophagic degradative pathways (Ding et al, 2019;Fujita et al, 2017;Lorincz et al, 2017;Lund et al, 2018).…”
Section: Tubule-shaped Vesicular Membranes Accumulate At the Trans-gosupporting
confidence: 84%
See 2 more Smart Citations
“…However, we detected a 3fold increase in the incidence of somatic structures resembling autophagocytic organelles in rab2 mutants ( Fig. S5D), potentially interesting in connection with the previously reported function of RAB2 in autophagic degradative pathways (Ding et al, 2019;Fujita et al, 2017;Lorincz et al, 2017;Lund et al, 2018).…”
Section: Tubule-shaped Vesicular Membranes Accumulate At the Trans-gosupporting
confidence: 84%
“…Of note, a subfraction of the ectopic LAMP1 accumulations in rab2 mutant were devoid of BRP signal and thus apparently not associated with early presynaptic precursor fields (Fig. S6C,D), potentially related to the previously described function of RAB2 in autophagic and lysosomal degradation (Ding et al, 2019;Fujita et al, 2017;Lorincz et al, 2017;Lund et al, 2018). In summary, these data suggest that at an early RAB2 dependent step of precursor biogenesis presynaptic proteins sort out of the Golgi on independent routes, separating active zone scaffold from SV/LAMP1 proteins.…”
Section: Convergence Of Golgi "Trafficking Streams" In the Maturationsupporting
confidence: 51%
See 1 more Smart Citation
“…In this study, we examined the expression level of FAM134B to evaluate the ER-phagy. FAM134B is an ER-resident receptor that facilitates ER degradation by autophagy via binding to autophagosomes (Murrow and Debnath, 2013;Khaminets et al, 2015;Grumati et al, 2018;Liang et al, 2018;Ding et al, 2019;Forrester et al, 2019;Wilkinson, 2019a,b). Our data showed that Grp78, FAM134B, p62, and cleaved caspase-3 were increased in the spinal cord of the SNL group compared with the sham group at postoperative days 7 and 14.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we and others reported that Rab2 is critical for biogenesis of mature degradative endoand autolysosomal compartments by controlling the fusion of late endosomes (LEs) with lysosomes and transport vesicles carrying lysosomal membrane proteins, and fusion of autophagosomes with endolysosomal organelles (Lorincz et al, 2017;Lund et al, 2018) (Ding et al, 2019).…”
Section: Introductionmentioning
confidence: 99%